Comparative Study of “Equivalence Scale” for Iranian Urban Households; Before and after Implementation of Targeted Subsidies Plan - fatemeh mirmohammadalitajrishi; teymour mohammadi; Ali Asghar Salem (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2018)
Expenditure pattern across households varies due to differences in their economic circumstances, household size and composition. So, movements in prices of goods over time will have different impacts on households. “Equivalence scale” is an index that enables us to do welfare comparisons and measurements of poverty and inequality across heterogeneous households, under consideration of households’ demographic characteristics and economies of scale in consumption. Implementation of targeted subsidies policy in Iran that has made significant price variations in recent years, has changed Iranian households’ equivalence scale. In this research, the urban households’ equivalence scale and variation of relative cost of a child was estimated using PS-QUAIDS and nonlinear Seemingly Unrelated Regressions (SURs), applying Iranian household's budget dataset for 2008 to 2012. Results indicate that the cost of an urban child is equal to 13 percent of an adult for 2008 until 2010 and the targeted subsidies policy has a negative and significant impact on equivalence scale.